ANALISIS KAJIAN RESEP DAN WAKTU TUNGGU PADA PERESEPAN KERTAS DAN ELEKTRONIK NONRACIKAN DI SALAH SATU KLINIK - Wikaningtyas, Pratiwi; Shafira, Riyani Intan (School of Pharmacy Institut Teknologi Bandung, 2025)
Prescription service is a written request from a doctor to a pharmacist to provide and deliver medication for patients and it could prevent medication errors. Prescription service and waiting time are important points in pharmaceutical services. . Electronic prescription can minimize the incidence of medication errors and reduce waiting time. This study was conducted to compare paper-based prescriptions and electronic prescriptions on medication errors and waiting time using an analytical observational method with a cross-sectional study design. Data was collected prospectively using prescription review. Qualitative data was analyzed using Chi-Square and quantitative data was analyzed using Wilcoxon Rank Sum Test. The results showed the average number of medication errors was higher in paper-based prescriptions (10.66%) than in electronic prescriptions (5.82%). The waiting time was longer for paper-based prescriptions (10 minutes 10 seconds) compared to the average for electronic prescriptions (8 minutes 23 seconds). The results showed that the implementation of electronic prescriptions in one of the clinics is better than paper prescriptions.